Report on General Elections, Pak.1970-71 - Election Commission, Pak (Karachi, Manager of Publications, 1972)
Introduction, Legal Framework for elections, Electoral rolls, Delimitation of constituencies, programme of elections.
Keywords: Elections --Pakistan.